Criticism and Analytical Review on the Art Chapter of the An Essay on Man - Reza Mirmobin; Ali Moradkhani; Seyed Abdol Majid Sharifzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The Ernest Cassirer Symbolist Philosophy was one of the most important systematic philosophical thoughts of the twentieth century, which did not spread as many times as it deserved and was not introduced in principle. One of these reasons was the lack of author’s conclusive work on his philosophy. But at the end of his life, he wrote a book for English speakers, which is an entry into this thinking. The book, An Essay on Man, was translated from French translation to Persian. This book was important because of an independent chapter on art which the philosopher did not have time to review. The present article intends to correct the mistakes by reviewing the Persian text with the English text of the chapter and provide a small field for understanding this valuable and succinct chapter. So, there is no intention of criticizing the translator and only to facilitate the understanding of the topic for the Persian speaker.